Exploiting avian vision with aircraft lighting to reduce bird strikes - Blackwelll, Bradley F.; DeVault, Travis L.; Seamans, Thomas W.; Lima, Steven L.; Baumhardt, Patrice; Fernández-Juricic, Esteban (DigitalCommons@University of Nebraska - Lincoln, 2012)
1. Bird–aircraft collisions (bird strikes) represent a substantial safety concern and financial burden to civil aviation world-wide. Despite an increase in the rate of damaging bird strikes, necessary steps to develop a mitigation method outside of the airport environment have not been empirically tested. 2. We assessed whether use of aircraft lighting might enhance detection of and reaction to the approach of an aircraft in flight by Canada geese Branta canadensis Linnaeus, a species responsible for a high rate of damaging bird strikes. We used a novel approach by estimating the visibility to the goose visual system of a standard radio-controlled (RC) aircraft (standard aircraft) exhibiting either a 2-Hz alternating pulse of two lights, or lights off; and another RC aircraft designed to mimic a raptor (predator model). We then exposed wing-clipped Canada geese to the approach of each aircraft and quantified behavioral responses to respective treatments. 3. Estimates of chromatic and achromatic contrasts indicated that the standard aircraft with lights on was more salient to the visual system of the Canada goose than with lights off or the predator model. 4. At individual and group levels, quicker alert responses were observed to the standard aircraft with lights compared with the lights off and predator model. Goose groups showed similar responses to approaches by the standard aircraft and the predator model, suggesting use of anti-predator behavior to avoid the aircraft. 5. Synthesis and applications. Understanding animal sensory ecology and associated behaviors can aid the development of methods exploiting certain behaviors to reduce negative human– wildlife interactions. For example, reducing the frequency of bird strikes requires the integration of wildlife management efforts within and outside of the airport environment that target species resource use and response to disturbance, with mitigation techniques focused on the aircraft. Moreover, the design of aircraft lighting systems to enhance detection and ...